Gamma-gamma coincidence performance of LaBr3:Ce scintillation detectors vs HPGe detectors in high count-rate scenarios. (April 2017) - Drescher, A.; Yoho, M.; Landsberger, S.; Durbin, M.; Biegalski, S.; Meier, D.; Schwantes, J.
Abstract: A radiation detection system consisting of two cerium doped lanthanum bromide (LaBr3 :Ce) scintillation detectors in a gamma-gamma coincidence configuration has been used to demonstrate the advantages that coincident detection provides relative to a single detector, and the advantages that LaBr3 :Ce detectors provide relative to high purity germanium (HPGe) detectors. Signal to noise ratios of select photopeak pairs for these detectors have been compared to high-purity germanium (HPGe) detectors in both single and coincident detector configurations in order to quantify the performance of each detector configuration. The efficiency and energy resolution of LaBr3 :Ce detectors have been determined and compared to HPGe detectors. Coincident gamma-ray pairs from the radionuclides 152 Eu and 133 Ba have been identified in a sample that is dominated by 137 Cs. Gamma-gamma coincidence successfully reduced the Compton continuum from the large 137 Cs peak, revealed several coincident gamma energies characteristic of these nuclides, and improved the signal-to-noise ratio relative to single detector measurements. LaBr3 :Ce detectors performed at count rates multiple times higher than can be achieved with HPGe detectors. The standard background spectrum consisting of peaks associated with transitions within the LaBr3 :Ce crystal has also been significantly reduced. It is shown that LaBr3 :Ce detectors have the unique capability to perform gamma-gamma coincidence measurements in very high count rate scenarios, which can potentially benefit nuclear safeguards in situ measurements of spent nuclear fuel. Highlights: Development of LaBr3:Ce scintillation detectors for a gamma-gamma coincidence. Energy gating was successfully employed in reducing the background. ɣ-ɣ coincidence can be used in the identification of fission products in spent nuclear fuel.